A Novel System for Evaluating the Inhibition Effect of Drugs on Cytochrome P450 Enzymes in vitro Based on Human-Induced Hepatocytes (hiHeps) - Li, Yan; Lu, Ying-Yuan; Jia, Jun; Fang, Meng; Zhao, Lin; Jiang, Yong; Shi, Yan; Tu, Peng-Fei; Guo, Xiao-Yu (Frontiers in Pharmacology, 2021)
Cytochrome P450 (CYP) is the most important phase I drug-metabolizing enzyme, and the effect of drugs on CYP enzymes can lead to decreased pharmacological efficacy or enhanced toxicity of drugs, but there are many deficiencies in the evaluation models of CYP enzymes in vitro. Human-induced hepatocytes (hiHeps) derived from human fibroblasts by transdifferentiation have mature hepatocyte characteristics. The aim was to establish a novel evaluation system for the effect of drugs on CYP3A4, 1A2, 2B6, 2C9, and 2C19 in vitro based on hiHeps. Curcumin can inhibit many CYP enzymes in vitro, and so the inhibition of curcumin on CYP enzymes was compared by human liver microsomes, human hepatocytes, and hiHeps using UPLC-MS and the cocktail method. The results showed that the IC50 values of CYP enzymes in the hiHeps group were similar to those in the hepatocytes group, which proved the effectiveness and stability of the novel evaluation system in vitro. Subsequently, the evaluation system was applied to study the inhibitory activity of notoginseng total saponins (NS), safflower total flavonoids (SF), and the herb pair of NS–SF on five CYP enzymes. The mechanism of improving efficacy after NS and SF combined based on CYP enzymes was elucidated in vitro. The established evaluation system will become a powerful tool for the research of the effect of drugs on the activity of CYP enzymes in vitro, which has broad application prospects in drug research.